SISTEM INFORMASI PERPUSTAKAAN DIGITAL SMA ABC - Wina Witanti; Albi Fitransyah; Gumilar M. Sutrisna (PROCEEDING STIMA)
Libraries as the providers of services to users or visitors required methods of service that is fast, easy and efficient. The manual Library services will causing various problems in the provision of services such as service is slow, the difficulty of searching book collection and less accurate searching archived data. The Information and computer technology advances offering great opportunities to support the smooth task in many areas of life including the library field. Library as an institution is one of the information management field of application of information technology is growing rapidly. One feature that can be developed in the library field is the development of web-based digital library. Use of this web site provides easy access to information faster from both inside and outside the library. Therefore will be created web-based digital library is the alternative provision of services to overcome obstacles to access information in the library and the library service. The system is constructed with a model website using PHP script and My SQL database. With the development of digital library information system makes the members and officers it easier in the lending and the processing of data in the library at SMA ABC.Keywords: libraries, digital libraries, web.